MARKETING SUPPORT OF BUSINESS, CONSUMER AND STATE INTERACTION (Economic journal of Lesya Ukrainka Volyn National University, 2022)
This article develops the theoretical basis of the study of the marketing environment of the enterprise, in particular,the interaction of business, consumers (users, customers) and the state with the help of marketing tools. The need to findcommon rational solutions of the main economic actors – business, consumers and the state – to increase the pace ofinnovative transformations that meet national interests and aimed at economic development at all levels of governmentthrough the widespread use of marketing tools. Emphasis was placed on the urgent need for business cooperation withall economic actors in view of the rapid development of digital technologies, pandemic sentiment in society and theneed for cohesion. It is shown that the purpose of cooperation is mutually beneficial cooperation and the formation of astrong ecosystem of the country. The peculiarities and the main tasks of innovative marketing at the enterprise aresingled out and analyzed. The parameters of evaluating the effectiveness of entrepreneurial activity of the marketingsector with the help of financial and non-financial indicators of BSC are determined.
Keywords: marketing, business, consumer, IT, enterprises, innovations, state.